Chenopods, Chenopodium spp. - Partap, T.; Joshi, B.D.; Galwey, Nicholas W.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1998)
The cultivation of quinoa (Chenopodium quinoa) in the Americas is widespread and well researched. It is less well known that Chenopodium was a common component of farming systems in the hilly and mountainous regions of Asia, particularly the Himalayas, the Hangduan mountains and the chain of uplands extending beyond the eastern fringes of the Himalayas as far as Taiwan. Replacement by high yielding varieties of staple crops has led to a decline in their cultivation. With a shift in focus towards production on agriculturally marginal lands, particularly mountainous regions, Chenopodium has a role to play both as a nutritious food crop and as a cash crop. Chenopodium has a high grain protein content, compared with cereals, is able to survive and compete in intercropping systems and forms mycorrhizal associations which maximise their use of scarce nutrients. This monograph describes the genetic resources of Chenopodium under the chapter headings: introduction; history of chenopods in Asia; the chenopod farmers and farming; crop genetic resources: the chenopod landraces; reproductive system and breeding features; phenological and ecophysiological variation; promising features of chenopods; genetic resources conservation efforts; evaluation of genetic variability; introduction of quinoa in Asia; limitations of the crop; and research priorities for chenopod. An appendix lists institutions, professionals and others associated with Chenopodium crop conservation, research and development. (Abstract © CAB ABSTRACTS, CAB International)